Obmowa, osądzanie, narzekanie czy milczenie? Rozważania Ojców Pustyni - Łeńska-Bąk, Katarzyna Ewa; Dąsal, Mateusz (Vox Patrum, 2021)
The monastic movement was initiated by Saint Anthony at the end of the 3rd century. A new form of asceticism emerged, characterized by a severance from world and society: called anachoresis or hermitism. From that moment, the life of hermits is to be full of sacrifices, which include fasting, sexual abstinence, prayer and work, but also silence. It was believed that only in silence would a brother get a chance to meet God and hear His Word. Only then he or she would be able to lead others, thanks to the power of his or her love and humility. Keeping silence was an extremely important and frequent topic undertaken by the Desert Fathers in their aphophtegmata. The purpose of the paper is to focus on a certain kind of tension between silence and speech, and actually specific cases of spoken words, called by the Desert Fathers "bad words". They should be avoided above all, and they were always considered, among others, as slander, judgment and complaint. Various understandings of keeping silence will be indicated in the context of refraining from the above-mentioned abuse which should lead to spiritual growth of a younger generation of monks.